Differential contribution of basic residues to HIV-1 nucleocapsid protein’s nucleic acid chaperone function and retroviral replication - Wu, Hao (Oxford University Press, 2014)
The human immunodeficiency virus type 1 (HIV-1) nucleocapsid (NC) protein contains 15 basic residues located throughout its 55-amino acid sequence, as well as one aromatic residue in each of its two CCHC-type zinc finger motifs. NC facilitates nucleic acid (NA) rearrangements via its chaperone activity, but the structural basis for this activity and its consequences in vivo are not completely understood. Here, we investigate the role played by basic residues in the N-terminal domain, the N-terminal zinc finger and the linker region between the two zinc fingers. We use in vitro ensemble and single-molecule DNA stretching experiments to measure the characteristics of wild-type and mutant HIV-1 NC proteins, and correlate these results with cell-based HIV-1 replication assays. All of the cationic residue mutations lead to NA interaction defects, as well as reduced HIV-1 infectivity, and these effects are most pronounced on neutralizing all five N-terminal cationic residues. HIV-1 infectivity in cells is correlated most strongly with NC’s NA annealing capabilities as well as its ability to intercalate the DNA duplex. Although NC’s aromatic residues participate directly in DNA intercalation, our findings suggest that specific basic residues enhance these interactions, resulting in optimal NA chaperone activity.